PEMBAURAIN KOMUINITAS TIOINGHOA MUSLIM DI KUDUS 1961 - 1998 - Santoso, Budi; Puguh, Dhanang Respati (Sabda: Jurnal Kajian Kebudayaan, 2006)
This research discusses the assimilation process of Chinese moslem community in Kudus in the year 1961-1998 by using historical method. There are four factors which formed Chinese moslem community in Kudus, namely environment, education, marriage, and willingness. There are two unique typologies owned by Chinese moslem community, first, 'abangan'Chinese moslem and second, 'putihan' Chinese moslem. Behavioral configurations of social religiousness of abangan Chinese moslem still entangle ancestor's traditional procedures, such as doing worshiping to ancestor, celebrating Imiek, and installing to 'rajah' (tatto) Chinese. On the contrary, putihan Chinese moslem configurations have eliminated all ancestor's traditional procedures and they are active in running Islam teaching, like conducting shalat five times a day, holy fasting in ramadlan, zakat, and haji. The logical consequence from the assimilation process between Chinese moslem and native moslem is the decreasing orientation to ancestor's culture. The reduction orientation of the ancestor's culture can be seen from assimilation channels, such as name changing, marriage, communication and language, education, and earn living